Rare earth coordination dinuclear compounds constructed from 3, 5-dicarboxypyrazolate and succinate intermetallic bridges. (25th April 2016) - Lahoud, Marcelo G.; Muniz, Elaine C.; Arroyos, Guilherme; Fávaro, Marcelo A.; Davolos, Marian R.; D'Vries, Richard F.; Ellena, Javier; Freitas, Rafael S.; Arrighi, Everton; Frem, Regina C. G.
Abstract : We describe the synthesis, spectroscopic characterization and photoluminescence studies of a new family of rare earth compounds of formula [RE2 (dcpz)2 (suc)(H2 O)8 ]·(H2 O)1.5 . Abstract : In this paper we describe the synthesis of a new family of rare earth compounds of general formula [RE2 (dcpz)2 (suc)(H2 O)8 ]·(H2 O)1.5, where RE = Y (1 ), La (2 ), Ce (3 ), Pr (4 ), Nd (5 ), Sm (6 ), Gd (7 ), Tb (8 ), Dy (9 ), Ho (10 ), Er (11 ), Tm (12 ) and Yb (13 ); dcpz = 3, 5-dicarboxypyrazolate; suc = succinate. Single crystal X-ray diffraction studies showed that all the complexes are isostructural and crystallize in the triclinic system, space group P 1̄. They exist as dinuclear discrete molecules in which the metallic centers are linked together by dcpz and suc bridges. Hydrogen bonds between dimers give rise to a 3Dbcu supramolecular network with topology (4 24 ·6 4 ). Solid-state photoluminescence studies revealed that the ligand-to-metal energy transfer mechanism is responsible for the visible emission of Sm (6 ), Tb (8 ) and Dy (9 ) compounds while for (5 ), near-infrared (1060 nm) emission was obtained by the direct excitation f orbitals in the Nd 3+ ion. Magnetization measurements indicated antiferromagnetic interactions between the RE 3+ ions, except Y 3+ (1 ) and La 3+ (2 ).